Polarity-independent effects of transcranial direct current stimulation over the bilateral opercular somatosensory region: a magnetoencephalography study. Issue 13 (6th September 2017) - Nakagawa, Kei; Koyama, Soichiro; Inui, Koji; Tanaka, Satoshi; Kakigi, Ryusuke; Sadato, Norihiro
Abstract : The opercular somatosensory region (OP) plays an indispensable role in pain perception. In the present study, we investigated the neurophysiological effects of transcranial direct current stimulation (tDCS) over the OP. Somatosensory-evoked magnetic fields following noxious intraepidermal electrical stimulation to the left index finger (pain-SEFs) were recorded before and after tDCS with a single-blind, sham-controlled, cross-over trial design. Three tDCS conditions of left anodal/right cathodal tDCS, left cathodal/right anodal tDCS (each, 2 mA, 12 min), and sham tDCS (2 mA, 15 s) were applied. Despite the subjective pain sensation being unaltered, the two anodal (real) interventions significantly decreased OP activity associated with pain-SEFs. In conclusion, tDCS over the OP with the present parameters did not have a significant impact on pain sensation, but modulated its cortical processing.